Pemberdayaan Masyarakat Untuk Meningkatkan Ketahanan Pangan Melalui Budidaya Hidroponik di Desa Saka Kajang - Tiani, Agus; Ariyanti, Agustina; Stepani, Agnesia; Saiful, Ahmad; Firdaus, Husnandar Sigfried; Aryadi, Kavin; Bangun, Manuella Gibersim; Pasya, Muhammad Akmal; Kelvin, Muhmmad; Marcela, Nadila; Qammatasya, Norhaliza; Silvia, Reisa; Nakalelu, Saputri; Ari, Tommy Muhammad; Sefitri, Tri (Fakultas Teknik Universitas Palangka Raya, 2024)
This community service aims to strengthen food security in Saka Kajang Village through the implementation of hydroponic cultivation. PKM activities aim to encourage the community to adopt hydroponic plant cultivation. The methods used include socialization and training for PKK mothers regarding hydroponic cultivation techniques in greenhouses. The implementation of hydroponic cultivation includes coordination with the village government, preparation of materials and tools, construction of greenhouses, sowing seeds and planting vegetable seedlings, testing hydroponic equipment, socialization on maintenance methods, and division of ongoing maintenance tasks. The results of PKM show that the training and mentoring went as expected. Residents followed the process of making hydroponic installations, socialization, and directly implementing planting with hydroponic media. Harvest evaluations were carried out to overcome problems that arose during the planting of kale using hydroponic installations. This activity received appreciation from the village head